Immune checkpoint inhibitors in pancreatic adenocarcinoma: a systematic review and meta analysis of clinical outcomes - Al-Khinji, Aisha; Al-Korbi, Noora; Al-Kuwari, Sheikha; Al-Hor, Abdullatif; Malouche, Dhafer (Frontiers in Oncology, 2025)
BackgroundPancreatic ductal adenocarcinoma (PDAC) remains one of the most aggressive malignancies, with poor outcomes despite therapeutic advancements. Immune checkpoint inhibitors (ICIs) have transformed cancer care, but their efficacy in PDAC is limited due to the tumor’s immunosuppressive microenvironment.MethodsWe systematically reviewed and meta-analyzed clinical outcomes of ICI therapy in PDAC using studies from PubMed, CINAHL, Cochrane Library, and Google Scholar, published up to February 28, 2024. Eligible studies reported objective response rate (ORR), progression-free survival (PFS), or overall survival (OS). Risk of bias was assessed using RoB 2.0 and ROBINS-I. Random-effects models estimated pooled effect sizes.ResultsFifty-four studies (n = 2,364) were included. ORR ranged from 0% to 67%. ICI-based combinations showed a modest ORR benefit (OR = 1.10; 95% CI: 1.02–1.18) and improved OS when combined with chemotherapy (HR = 0.82; 95% CI: 0.78–0.87). However, ICIs plus radiotherapy were associated with increased mortality (HR = 1.18; 95% CI: 1.04–1.34). PFS improved in select subgroups, particularly in patients with high tumor mutational burden or mismatch repair deficiency.ConclusionICIs combined with chemotherapy may modestly improve survival in PDAC. Outcomes remain heterogeneous and limited, underscoring the need for better biomarker-driven patient selection and more effective combination strategies.